Strategi Bertahan Hidup Buruh Pengupas Kulit Udang dalam Pemenuhan Kebutuhan Dasar di Masa Covid-19 - Tuti Atika; Fajar Utama Ritonga; David Martua Tamba (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The outbreak of COVID-19 cases in all corners of the world has affected all sectors in human life, affecting the economic, educational, social and cultural sectors. However, the biggest impact of the COVID-19 outbreak is the economic sector, due to restrictions on human movement in order to break the chain of COVID-19, especially the informal sector economy, namely freelance daily laborers who work in shrimp skin stripping businesses. The purpose of this study is to describe the survival strategy of shrimp shell peeling workers in Tangkahan Village. The results of research and observations on research subjects found the fact that: (1) The Covid-19 pandemic caused an impact on workers due to the ban on export-import of goods from within and outside the country. (2) Shrimp Skin Peeling Workers use 3 survival strategies during the Covid-19 pandemic, namely: (a) An active strategy is to include family members, (b). The passive strategy is to save and reduce expenses in meeting food and clothing needs by eating potluck such as consuming instant noodles, tofu, tempeh and eggs, not buying new clothes. In addition, it also reduces social activities, (c) Network strategy is to borrow money from toke, family and relatives when in urgent conditions that need money.